2019
DOI: 10.1371/journal.pmed.1002951
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen systems to improve clinical care and outcomes for children and neonates: A stepped-wedge cluster-randomised trial in Nigeria

Abstract: BackgroundImproving oxygen systems may improve clinical outcomes for hospitalised children with acute lower respiratory infection (ALRI). This paper reports the effects of an improved oxygen system on mortality and clinical practices in 12 general, paediatric, and maternity hospitals in southwest Nigeria.Methods and findingsWe conducted an unblinded stepped-wedge cluster-randomised trial comparing three study periods: baseline (usual care), pulse oximetry introduction, and stepped introduction of a multifacete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(74 citation statements)
references
References 38 publications
0
74
0
Order By: Relevance
“…Our work has shown how to combine quality equipment and training to achieve context-appropriate and sustainable improvement in oxygen systems and improve clinical outcomes. 5,[11][12][13] This experience has informed the development of clinical and technical guidance by the World Health Organization (WHO) and the United Nations Children's Fund (UNICEF) [14][15][16] and is now informing oxygen scale-up for COVID-19 (Box).…”
Section: Lessons Learnedmentioning
confidence: 99%
See 2 more Smart Citations
“…Our work has shown how to combine quality equipment and training to achieve context-appropriate and sustainable improvement in oxygen systems and improve clinical outcomes. 5,[11][12][13] This experience has informed the development of clinical and technical guidance by the World Health Organization (WHO) and the United Nations Children's Fund (UNICEF) [14][15][16] and is now informing oxygen scale-up for COVID-19 (Box).…”
Section: Lessons Learnedmentioning
confidence: 99%
“…2 Pulse oximetry, with practical task-based training and simple guidelines, can enable health care workers to target oxygen toward those who need it most, dramatically improving patient oxygen access and clinical outcomes. 13 In contexts where pulse oximetry is not a standard of care, COVID-19 offers an opportunity to establish oxygen saturation as the "fifth vital sign." However, although pulse oximetry is a simple skill, it is a fundamentally new concept for many health care workers and will require encouragement and support to integrate it into the workflow.…”
Section: Box Essential Resources For Additional Information On Oxygementioning
confidence: 99%
See 1 more Smart Citation
“…Effective oxygen systems are an important element of quality hospital care and are critical for achieving good clinical outcomes for patients with severe pneumonia [1,2]. Improvements in hospital oxygen systems have been shown to reduce inpatient child mortality from pneumonia by 35-58%, yet oxygen access for patients remains poor in many low-and middle-income countries (LMICs) [3][4][5][6][7][8]. The COVID-19 pandemic has further highlighted the importance of improving hospital oxygen systems, and the fatal consequences of deficient systems, pushing oxygen access higher onto the global health agenda [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Results are published elsewhere [5,[16][17][18][19][20][21][22]. We found that the introduction of pulse oximetry and improved oxygen systems contributed to marked improvements in pulse oximetry and oxygen practices and was associated with reduced risk of death for children admitted with pneumonia, but not other illnesses [5]. Importantly, we observed the greatest impact on pneumonia mortality with the introduction of pulse oximetry (prior to implementing the full oxygen system) and received qualitative feedback that pulse oximetry may have had broader positive effects on other care practices [5,19].…”
Section: Introductionmentioning
confidence: 99%